Tathwir al-Mawad al-Ta’limiyyah Li Maharat al-Kalam min Khilali al-Nushush al-Qur’aniyyah li Thullab Ma’hadi al-Aimma al-‘Aliy al-Islamiy Malang Jawa al-Syarqiyyah - Harno Purwanto (University of Darussalam Gontor, 2022)
The development of speaking skills teaching materials is still needed. This is because there are still many students who are weak in speaking Arabic skills. Including students who memorize the Qur'an are also still weak in Arabic language skills. Even though the memorized verses of the Qur'an are Arabic sentences that are the most fluent and can improve and enrich vocabulary in Arabic. So this study aims to effectivity of teaching materials development for speaking skills through the Qur'anic texts for students of Ma'had 'Aliy Al Aimmah Malang, East Java. This study uses Research dan Development methods. The data obtained through the pretest and posttest of the students were then strengthened by the assessment of education experts and experts. The results of this study indicate that the application of this teaching material is statistically effective. Likewise, the education expert's assessment showed that 86% of these teaching materials were effectively applied, while the the Arabic Language and Al-Qur'an al-Kareem experts assessed that 89% of these teaching materials were feasible.